Информационное обеспечение для системы реографии легких - Величко, О. Н.; Карпенко, С. А. (ХНУРЭ, 2008)
Advantages and disadvantages of the method of delivery the rheogram of lungs for different respiratory phases were analyzed. Wavelet analysis advantages for research of rheogram fine structure for inspiration and expiration were revealed. The interpretation method of lung segment rheography results, based on digital wavelet analysis was offered
Keywords: реография легких; биомединженерия